Anti-Inflammatory Test of Topical Cream Preparations from Ethyl Acetate Fraction of Johar Leaves (Cassia siamea L.) in White Mice - Audri Nandia Apriyanti; Diah Pratimasari; Eka Wisnu Kusuma (Jurnal Farmasi (Journal of Pharmacy), 2023)
Johar leaves contain chemical compounds, there are alkaloids, saponins, tannins, flavonoids, barracol, sitosterol. This study aims to determine the anti-inflammatory effect of the johar leaf ethyl acetate fraction topically, to determine the optimum concentration of johar leaf ethyl acetate fraction in cream preparations, and to determine the physical properties of the johar cream and cream stability. The leaves of johar (Cassia siamea L.) were extracted using the maceration method with 70% ethanol. The ethanol extract of johar leaves was fractionated with water, n-hexane and ethyl acetate as solvents. The ethyl acetate fraction of johar leaves was made cream with a concentration of 2.5%, 5% and 10%. The basis and the three formulas were tested for the physical quality of the cream including the organoleptic test, homogeneity, viscosity, spreadability, adhesion, cream type, pH and cream stability. The anti-inflammatory effect was determined by measuring the thickness of the back skin of the mice. The data obtained were analyzed statistically One Way Anova with a confidence level of 95% to determine that there were significant differences between treatment groups. The results showed that the leaf ethyl acetate fraction cream could provide topical anti-inflammatory effects on carrageenan-induced white mice with an effective concentration of 5% with (% PI) of 36.67%. The ethyl acetate fraction of johar leaves with a concentration of 2.5% and 5% fulfilled the requirements for the physical properties of the cream, but the cream with a concentration of 10% did not meet the requirements in the pH test. And the ethyl acetate fraction cream of johar leaves was stable in 1 month storage